Compartive studies of parasitic plants\' haustorial system: structural and phylogenetic perspectives - Teixeira-Costa, Luíza (2019)
The parasitic life style has repeatedly evolved in several occasions within nearly every life kingdom. Among Plants, parasitic clades are currently believed to have diverged 12 times independently, comprising over 1% of all extant diversity of flowering plants (Angiosperms). This great variety of species is translated into a wide array of plant habits, body sizes, modes of host infestation, photosynthetic capacity, life cycles, occupied environments, etc. Still, all of these ca. 4,600 plant species are united by the presence of a particular organ known as haustorium. Said to \"morphologically define parasitism among plants\", this peculiar plant organ carries out the main parasitic functions, from initial attachment and invasion of host tissues, to the stablishmente of a morpho-functional bridge that allows parasite-host communication and substance exchange. Considering the importance of this organ for the parasitic plant lifeform, the wide diversity of these plants is analyzed here in terms of structural and evolutionary aspects of the haustorium development. Initially, detailed studies are presented for the species characterized by two infestation modes: mistletoes, i.e., parasites the attach to host stems and branches; and endophytic parasites, i.e., plants that colonize the interior of the host body and are only visible outsite the host during the reproductive phase. Regarding mistletoes, details obtained from broad studies on their haustorium morphogenesis were used for a phylogenetic analysis of ancestral character state reconstruction and divergence time estimations. Results suggest that the change from root to aerial parasitism could have been facilitated by a common background for haustorium development shared by root parasites and early diverging mistletoes. From these early ancestors, specialization of haustorium tissue located internally to the host stems/branches would have led to evolution of different morphologies of the host-parasite connection, including the rise of a few endophytic species within mistletoe clades. In the second chapter, endoparasitism is detailed and discussed, including endophytic mistletoes but mainly focusing on the four puzzling plant families exclusively composed of species showing this infestation mode. Despite their reduced body size and endophytic system initially composed of parenchyma cells only, endoparasitic species of these four families are shown here to differentiate conductive phloem and/or xylem cells. Different strategies for the establishment of host-parasite connections are also reported and discussed as probably related to flower size. The hypothesis of parasitic plant control over host cambium differentiation is highlighted as a likely explanation for the alterations observed in host xylem and phloem anatomy. In the sequence, the third chapter is dedicated to a study of the terminology related to haustorium morphology and anatomy. A total of 48 terms are presented and discussed in an illustrated and referenced glossary. As the main result, parasitic plant haustorium is understood as a complex organ, composed of different tissues and cell types. The frequent equalization of this complete organ with one of its parts is discussed as frequently leading misunderstandings of the very parasitic nature of some species and lineages of haustorium-forming plants. Finally, the fourth chapter provides a broad comparative study of this peculiar organ in all 12 independent lineages of parasites. Methods in plant morphology and anatomy were combined with the current phylogenetic paradigm of parasitism evolution among plants. A general developmental sequence is discussed to be common in all haustoria, despite their varied ontogenetic origin. In all analyzed parasitic clades, direct host-parasite xylary connections were formed; on the other hand, phloem connections were detected in species of four clades only. A comparison between the huadotium and other plant organs discusses terminal haustoria to be a modified root, while lateral haustoria could be interpreted as either a modified stem, or as neoformation. Altogether, these results indicate the existence of very conservative mechanisms for haustorium formation throughout all of its diversity